Effect of Concept Mapping Teaching Approach on Students’ Academic Performance in Chemistry in Senior Secondary Schools - Torpev Terver Francis; Salaudeen Jaleel Baba (Indonesian Journal of Educational Research and Technology, 2023)
This study investigated the effect of the concept mapping teaching approach on students’ performance in Chemistry in senior secondary schools regarding a periodic table concept. W analyzed 11,094 chemistry students from eleven public senior secondary schools in Katsina. Two schools and 128 Senior Secondary chemistry students formed the sample for the study. Three research questions with hypotheses were raised and formulated respectively to guide the study. The study was a non-equivalent pre-test and post-test control group involving one experimental group and one control group. The chemistry Performance Test was used for data collection. The study revealed that there is no significant difference in the mean performance scores of students taught a periodic table concept using concept mapping and those taught the same concept before the treatment. There is a significant difference in the performance of the students taught a periodic table concept using concept mapping and those taught the same concept using a conventional teaching method after the treatment. Also, there is no significant difference in the mean performance score that exists between male and female chemistry students.